2021
DOI: 10.1029/2020ja029057
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Loss Timescales of Slot Region Electrons due to Plasmaspheric Hiss Based on Van Allen Probes Observations

Abstract: Plasmaspheric hiss can be regarded as an incoherent, broadband electromagnetic whistler mode emission with frequencies ranging from ∼20 to ∼2 kHz (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 56 publications
(108 reference statements)
0
11
0
Order By: Relevance
“…(2021) further demonstrated that diffusion simulations of electron loss due to plasmaspheric hiss are sensitive to variability time scales, which revealed more diffusion from averaged diffusion coefficients calculated for individual observation‐specific diffusion coefficients than when the diffusion coefficients are constructed from averaged inputs. Nevertheless, constructing the diffusion coefficients using averaged inputs is still an important method that numerous studies relied on to reproduce the essential feature of the radiation belt electron dynamics (e.g., Claudepierre et al., 2020; D. Wang & Shprits, 2019; D. Wang et al., 2019; Horne et al., 2013; Hua et al., 2020; H. Zhu et al., 2019; L. T. Li et al., 2017; Q. Zhu et al., 2021). Therefore, understanding the effects of uncertainties in the key inputs of the radiation belt electron simulation is a prerequisite to improve the radiation belt model performance, confidence, and forecasting accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…(2021) further demonstrated that diffusion simulations of electron loss due to plasmaspheric hiss are sensitive to variability time scales, which revealed more diffusion from averaged diffusion coefficients calculated for individual observation‐specific diffusion coefficients than when the diffusion coefficients are constructed from averaged inputs. Nevertheless, constructing the diffusion coefficients using averaged inputs is still an important method that numerous studies relied on to reproduce the essential feature of the radiation belt electron dynamics (e.g., Claudepierre et al., 2020; D. Wang & Shprits, 2019; D. Wang et al., 2019; Horne et al., 2013; Hua et al., 2020; H. Zhu et al., 2019; L. T. Li et al., 2017; Q. Zhu et al., 2021). Therefore, understanding the effects of uncertainties in the key inputs of the radiation belt electron simulation is a prerequisite to improve the radiation belt model performance, confidence, and forecasting accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many previous studies (e.g., Ni et al, 2008Ni et al, , 2014Ni et al, , 2016Gu et al, 2012;Summers et al, 2007;Thorne et al, 2010Thorne et al, , 2013Zhao et al, 2019;Zhu et al, 2021) have demonstrated that the long-term wave-particle effect is dominated by hiss and chorus waves for sub-MeV electron dynamics. However, during the active geomagnetic periods, the scattering effect by multiple wave modes can be significant for radiation belt dynamics in terms of the short-time effect.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The empirical models of electron lifetime due to chorus wave or hiss wave pitch angle scattering are applied to determine the loss term 𝐴𝐴 − 𝑓𝑓 𝜏𝜏 (Gu et al, 2012;Zhu et al, 2021). Inside the empirical plasmapause location (Carpenter & Anderson, 1992), the electron lifetime is dominated by 𝐴𝐴 𝐴𝐴hiss obtained from the empirical model of slot region hiss induced electron loss timescales by Zhu et al (2021), while outside the plasmapause, we use the electron lifetime 𝐴𝐴 𝐴𝐴chorus parameterized by Gu et al (2012). The 4.5-hr resolution PSD derived from flux observation at the highest available L is used as the outer boundary condition for the 4.5-hr intervals, while a constant inner boundary condition is used at ∼1.1 𝐴𝐴 𝐴𝐴𝐸𝐸 .…”
Section: -D Modeling Of Radial Diffusion and Convectionmentioning
confidence: 99%